STUDENTS' CREATIVE THINKING ABILITY PROFILE IN MATHEMATICS LESSONS OF RIAU PROVINCE - Fadilla, Jihan; Ainirohmah, Nailu; Marwaziah, Nirmala; Hafizah, Nur; Hayu, Sri Rah; Andrian, Dedek; Nofriyandi Nofriyandi; Mefa Indriati (UIR PRESS, 2024)
This study aims to describe students' creative thinking skills in mathematics. The type of research used in this research is descriptive research. The population in this study were junior high school level students in Bengkalis Regency, Riau while the sample was 59 students in the Bathin Solapan District and 50 students from the Bandar Laksamana sub-district. The sampling technique in this study was simple random sampling. The data collection technique in this study was a survey using a questionnaire instrument. Before the instrument is used, the instrument in the form of a questionnaire is validated in terms of content and construct. In terms of content, validity analysis uses the Aiken formula and CFA First Order, while construct validity uses CFA Second Order. Data analysis in this study used descriptive statistics. The results obtained from the analysis of students' creative thinking abilities in mathematics at the junior high school level show that the indicators of Elaboration, Flexibility, Originality, and Fluency in students' creative thinking abilities, obtain a good category percentage of 22.02% and a bad category of 77.98% .